Effect of materials selection on the minimum cost for optimal design of reinforced concrete beams using hill climbing algorithm - Hassajan, Sombut; Lamom, Alongkorn; Cheerarot, Raungrut (Asia-Pacific Journal of Science and Technology, 2017)
This research is to study the effect of materials selection on the minimum cost for optimal design of reinforced concrete simple beams using Hill Climbing Algorithm. Cross sections of simply supported beams under uniform load were designed for bending and shear strength according to standard of the Engineering Institute of Thailand (E.I.T. 1008-38 strength design method). The total cost of beams was calculated from materials and labor costs. From the study, it was found that the selection of steel grade affected the minimum cost of beams more than that of compressive strength of concrete. Considering the selection of steel grade, it can be seen that SD40 gave the lower minimum total cost than that of SD30 for all compressive strength levels. From the result, it can be concluded that the Hill Climbing Algorithm can help to study the effect of materials selection on the minimum cost for optimal design of reinforced concrete simply supported beams.